Assessing modern challenges and threats affecting national security by full-scale military operations - Ignatiev, Andrii; Burlakov, Serhii; Terletskii, Anatoliy; Skryl, Sergii (DIXI, 2025)
The concept of state security is widely recognized as a fundamental pillar in safeguarding a nation’s security environment, particularly against both external and internal threats. These threats, whether acting individually or collectively, complicate the functioning of state institutions, civil society, and other critical sectors. A persistent challenge in this domain is the deliberate creation of an artificially manipulated information environment, which significantly shapes public consciousness and fosters sentiments hostile to the state and its core attributes. This phenomenon manifests through the spread of misleading narratives, various forms of illegal activity, and psychological destabilization. Beyond their societal impact, such threats pose a direct risk to the state’s territorial integrity, sovereignty, and independence. They also undermine the democratic decision-making process, weaken national defense capabilities, and hinder the population’s ability to actively participate in national resistance efforts. Among the specific challenges to state security, the protection of critical infrastructure is particularly vital, with energy infrastructure emerging as a primary target of enemy attacks in the context of the Russian-Ukrainian war. Additionally, cyberspace remains highly vulnerable, underscoring the urgent need for a comprehensive real-time cybersecurity analytics system to safeguard critical infrastructure. Furthermore, advancing scientific research in the defense sector is essential. Interdisciplinary studies focused on security-related innovations play a crucial role in enhancing national defense strategies. Such research should analyze the experiences of Ukraine’s security and defense forces in adapting to modern combat methods, including the deployment of unmanned aerial vehicles and other advanced technologies.